2020
DOI: 10.1017/jfm.2020.211
|View full text |Cite
|
Sign up to set email alerts
|

Classical and symmetrical horizontal convection: detaching plumes and oscillations

Abstract: Classical and symmetrical horizontal convection is studied by means of direct numerical simulations for Rayleigh numbers Ra up to 3 × 10 12 and Prandtl numbers Pr = 0.1, 1 and 10. For both set-ups, a very good agreement in global quantities with respect to heat and momentum transport is attained. Similar to Shishkina & Wagner (Phys. Rev. Lett., vol. 116, 2016, 024302), we find Nusselt number Nu versus Ra scaling transitions in a region 10 8 Ra 10 11 . Above a critical Ra, the flow undergoes either a steady-os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 34 publications
3
24
0
Order By: Relevance
“…Such observation of scaling transitions further demonstrates that there are no pure scaling laws in thermal convection. This has already been seen in RBC (Grossmann & Lohse 2000;Ahlers et al 2009), horizontal convection Shishkina & Wagner 2016;Reiter & Shishkina 2020) and internally heated convection (Wang et al 2020b), and apparently crossovers between different scaling regimes also occur here. However, the sharpness of the scaling transition from β = 1/4 to β = 1/3 observed here is quite different from the smooth transition seen in RBC.…”
Section: Global Heat and Momentum Transport And Dissipation Ratessupporting
confidence: 81%
“…Such observation of scaling transitions further demonstrates that there are no pure scaling laws in thermal convection. This has already been seen in RBC (Grossmann & Lohse 2000;Ahlers et al 2009), horizontal convection Shishkina & Wagner 2016;Reiter & Shishkina 2020) and internally heated convection (Wang et al 2020b), and apparently crossovers between different scaling regimes also occur here. However, the sharpness of the scaling transition from β = 1/4 to β = 1/3 observed here is quite different from the smooth transition seen in RBC.…”
Section: Global Heat and Momentum Transport And Dissipation Ratessupporting
confidence: 81%
“…This suggests that the rest of the HC flow remains to be rather laminar. The change of the scaling form in the hot region with growing is consistent with the change of the dependence on observed by Reiter & Shishkina (2020).…”
Section: Discussionsupporting
confidence: 89%
“…For , the Nusselt number can be approximately expressed by . Recent DNS results (Reiter & Shishkina 2020) revealed that the heat transport dynamics undergoes several transitions from steady state to chaotic state as increases. For , the data start to oscillate at and transit to a chaotic state at .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations